Fungsi ASEAN Intergovernmental Commision on Human Rights (AICHR) Dalam Perlindungan HAM Di Wilayah Domestik Myanmar - Christa Delani Pelupessy; Josina Augustina Yvonne Wattimena; Wilshen Leatemia (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Human rights have not been of particular concern at the inception of ASEAN. Until then, there were several cases of human rights violations that occurred in the ASEAN region.Purposes of the Research: The aim of this writing is to study and delve the Role of AICHR in protecting Human Rights in domestic Myanmar. Methods of the Research: The method used is a normative juridical research method using statutory approach, conceptual approach, and case approach.Results of the Research: The results obtained from the research, it is proven that ASEAN Integovernmental Commission AICHR has fulfilled its function to protect Human Rights conflict in domestic Myanmar. AICHR seeks to obtain information on Human Rights violations occured in the domestic territory of Myanmar, and apply regular approach as well in dealing with issue of Human Rights violations in Myanmar which considered to be the function of AICHR Commission. The efforts managed by AICHR to protect Human Rights in Myanmar domestic territory are conducting consultations and discussions with the state of Myanmar, and holding workshops to discuss Human Rights violations on regional level together with ASEAN member countries for any Human Rights violations occured in Myanmar's domestic territory. AICHR endeavour to comply with ASEAN Principles poured in the ASEAN Charter, abides The Principle of Respect for State Sovereignty and The Principle of Non-Intervention.